Convergence of iterates of uniformly L-Lipschitzian and generalized asymptotically nonexpansive mappings in CAT(0) spaces - Suantai S. (Watam Press, 2014)
We study strong and Δ-convergence of a modified S-type iteration process inspired by Agarwal, O'Regal and Sahu (2007) for uniformly L-Lipschitzian and generalized asymptotically nonexpansive mappings in CAT(0) spaces. Copyright © 2014 Watam Press.